WEIGHT PERCEPTIONS AND THEIR IMPACT ON THE RELATIONSHIP BETWEEN WEIGHT AND HEALTH - Neto, D. D.; Baptista, T. M.; Marques, C.; Ferreira, A. S. (XVI European Congress of Psychology, 2019)
The present study analyzes the mediating role of weight distortion and weight self-criticism in the relationship between actual weight and perceived health, well-being, body satisfaction and emotional eating. 806 individuals were selected from a Portuguese national study on nutrition. They were divided into two groups according to self-reported dieting. A multiple mediation model was estimated using Structural Equation Modeling (SEM). A valid model was obtained in which weight self-criticism is a partial mediator of the relationship between weight and body satisfaction and a full mediator of the relationship between weight and emotional eating for the non-dieter group. For the dieter group, full mediation of weight self-criticism is observed in the relationships between weight and health, well-being and body satisfaction. For weight distortion, no mediation effect is found in either group. The results highlight the importance of weight perceptions in understanding the influence of body weight on several aspects of health and well-being. The type of weight perception is also relevant. A critical attitude towards weight is more determinant than the distortion in weight appraisal.